Salt production techniques in ancient China: the Aobo tu - Yoshida, Tora (Sinica Leidensia, 1993)
The Aobo tu , the 'Illustrated Boiling of Sea Water', was completed and published by Chen Chun in 1334. It is the world's earliest extant work exclusively dealing with salt production and salt production techniques. The first part of this book focuses on the technical, fiscal, administrative, social and economic background of the Aobo tu . It also provides the reader with information on the various editions and related material. This is followed by a complete annotated translation and the reproduction of two different sets of illustrations. By combining research on various aspects of the salt industry during the Song (960-1279) and Yuan (1271-1368) periods, a better understanding of the fiscal and economic importance of this crucial sector can be gained